Eco-innovation activities in the Czech economy 2008-2014: Impact of the eco-innovative approach to the profit stream and differences in urban and rural enterprises - Marek Vokoun; Jiřína Jílková (Economies, 2020)
The environmental benefits from the eco-innovation activities of enterprises have the nature of reduced material or water use per unit of output, less pollution and waste, better CO2 "footprint" in production and subsequent business processes. The socioeconomic impacts are associated with circular economy benefits like reduced energy use, decreased pollution and waste, and well-organized recycling possibilities of the product after use. The goal of this paper is to evaluate this innovative approach in the Czech economy. The hypotheses are aimed at the localization of enterprises, appropriability, and characteristics of enterprises that introduce eco-innovations to markets. The dataset is provided by the Czech Statistical Office and contains observations about the innovation activities of firms. Eco-innovation was surveyed in 2008 and 2014. This paper utilizes the estimation principles of CDM (Crépon, Duguet, and Mairesse) method at the firm level. The results suggest that rural-urban separation has no impact on the financial R&D intensity but urban enterprises have a higher probability to engage in innovation activities. The probability to introduce new-to-the-market innovations and eco-innovations is not dependent on localization. High-tech and knowledge-intensive industries have a lower probability to introduce eco-innovations to the market. The change in localization of enterprises to rural areas contributed to the higher sales form innovated goods and services. Higher appropriability was also observed in product eco-innovators. This paper offers a synthesis of factors that stimulate eco-innovation and shows that eco-innovation is a viable and sustainable innovative approach for rural and urban enterprises and identifies directions for future research.
Keywords: O31; O18; R11; 330; environmental; green; innovative; localization; production; rural; sustainability